Preoperative Immunotherapy in the Multidisciplinary Management of Oral Cavity Cancer - Philips, Ramez; Han, Chihun; Swendseid, Brian; Curry, Joseph; Argiris, Athanassios; Luginbuhl, Adam; Johnson, Jennifer (Frontiers in Oncology, 2021)
Despite advances in multimodal treatment for oral cavity squamous cell carcinoma, recurrence rates remain high, providing an opportunity for new therapeutic modalities that may improve oncologic outcomes. Much recent attention has been paid to the molecular interactions between the tumor cells with the adjacent peritumoral microenvironment, in which immunosuppressive molecular changes create a landscape that promotes tumor progression. The rationale for the introduction of immunotherapy is to reverse the balance of these immune interactions in a way that utilizes the host immune system to attack tumor cells. In the preoperative setting, immunotherapy has the advantage of priming the unresected tumor and the associated native immune infiltration, supercharging the adaptive anti-tumor immune response. It also provides the basis for scientific discovery where the molecular profile of responders can be interrogated to elucidate prognostic markers to aid in future patient selection. Preoperative immunotherapy is not without limitations. The risk of surgical delay due to immune adverse events must be carefully discussed by members of a multidisciplinary treatment team and patient selection will be critical. One day, the discovery of predictive biomarkers may allow for algorithms where pre-surgical immunotherapy decreases the size of surgical defect and impacts the intensity of adjuvant therapy leading to improved patient survival and decreased morbidity. With further study, immunotherapy could become a key component of future treatment algorithm.